THE QUANTIFIABLE COMPONENT OF QUALITY MANAGEMENT IN ENERGETIC INDUSTRY - CLAUDIA ISAC (Annals of the University of Petrosani: Economics)
The present paper intends to highlight aspects of the quality management characteristic to the energetic industry and particularly its distribution. The items listed are just a part of a more extensive research in this area and it focuses mainly on quantifiable items such as general and guaranteed performance indicators which prove that quality can be quantified and is not an unquantifiable component. The quality indicators presented demonstrate that the energetic system, including the quality management system can be included in the European trends and the alignment to these trends is compulsory considering the characteristics of the continuous product flow and of the non-stock items within this system.